Precision synthesis of graft copolymers via living cationic polymerization of p‐acetoxystyrene followed by friedel–crafts‐type termination reaction. Issue 21 (23rd August 2013) - Shinke, Yu; Yamamoto, Hidehiro; Kanazawa, Arihiro; Kanaoka, Shokyoku; Aoshima, Sadahito
ABSTRACT This study describes a novel precision synthesis strategy for graft copolymers using Friedel–Crafts‐type termination reaction between a cationically prepared poly(styrene derivative) and the naphthyl side groups from a poly(vinyl ether) main chain. The pendant alkoxynaphthyl groups on the poly(vinyl ether) efficiently terminated the living cationic polymerization of p‐acetoxystyrene (AcOSt) with SnCl4 in the presence of ethyl acetate as an added base. This research provides the first example of a well‐defined graft copolymer prepared using this method. The resulting polymer contained 40 poly‐(AcOSt) branches, as calculated from the Mw determined via gel permeation chromatography–MALS analysis, which was in good agreement with the estimated number of branches obtained from 1H NMR analysis. The acetoxy groups in the grafted poly(AcOSt) chains were easily converted into phenolic hydroxy groups under basic conditions. The as‐obtained graft copolymer with poly(p‐hydroxystyrene) side chains exhibited a pH‐sensitive phase separation in water. The synthetic method for preparing the graft copolymers was also effective in the living cationic polymerizations of other styrene derivatives. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 4675–4683